2004
DOI: 10.1128/jvi.78.24.13966-13974.2004
|View full text |Cite
|
Sign up to set email alerts
|

A DNAβ Associated with Tomato Yellow Leaf Curl China Virus Is Required for Symptom Induction

Abstract: We report here that all 25 isolates of Tomato yellow leaf curl China virus (TYLCCNV) collected from tobacco, tomato, or Siegesbeckia orientalis plants in different regions of Yunnan Province, China, were associated with DNA␤ molecules. To investigate the biological role of DNA␤, full-length infectious clones of viral DNA and DNA␤ of TYLCCNV isolate Y10 (TYLCCNV-Y10) were agroinoculated into Nicotiana benthamiana, Nicotiana glutinosa, Nicotiana. tabacum Samsun (NN or nn), tomato, and petunia plants. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
320
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(335 citation statements)
references
References 31 publications
12
320
1
Order By: Relevance
“…We demonstrated previously that TYLCCNV alone produces asymptomatic infections in tobacco, tomato, and petunia (Petunia hybrida) and that TYLCCNB is required for the production of leaf curl symptoms in these hosts (Cui et al, 2004). These studies showed that the bC1 protein encoded by TYLCCNB is a pathogenicity factor that is necessary for symptom production.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…We demonstrated previously that TYLCCNV alone produces asymptomatic infections in tobacco, tomato, and petunia (Petunia hybrida) and that TYLCCNB is required for the production of leaf curl symptoms in these hosts (Cui et al, 2004). These studies showed that the bC1 protein encoded by TYLCCNB is a pathogenicity factor that is necessary for symptom production.…”
Section: Discussionmentioning
confidence: 80%
“…We demonstrated previously that transgenic N. benthamiana, tobacco, and Arabidopsis plants expressing the TYLCCNB bC1 gene are stunted and show leaf cupping and curling. The resulting "symptoms" are much more severe than those associated with TYLCCNV plus TYLCCNB infection, demonstrating that bC1 is very toxic to plants (Cui et al, 2004;Yang et al, 2008). SnRK1 phosphorylation of bC1 may be used by plants to overcome its detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because begomo-viruses can systemically infect N. benthamiana in the absence of DNA-b (Fig. 1a-d) and non-functional satellites can be maintained in plants (Cui et al, 2004;Saunders et al, 2004;Saeed et al, 2005), the inability to detect a satellite in systemically infected tissues suggests trans-replication incompatibility rather than a defect in satellite systemic movement mediated by the helper virus. With the exception of CLCuMV, which could maintain a low level of EpYVV DNA-b replication that was not detected in systemically infected tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%